Volatile organic compound and methane emissions from well development operations in the Piceance Basin - Hilliard, Noel G., author; Collett, Jeffrey L., advisor; Fischer, Emily V., committee member; Ham, Jay M., committee member; Hecobian, Arsineh, committee member (Colorado State University. Libraries, 2016)
The natural gas industry in Colorado has experienced significant growth in the last decade due to widespread use of unconventional natural gas extraction technologies. Garfield County is located in the Rocky Mountain Region on the western slope of Colorado above the Piceance Basin. Natural gas wells in this region penetrate the William’s Fork formation, located approximately 4,000 ft. below the surface, which is a tight sand formation known to be rich in natural gas. Horizontal drilling increases the extraction potential of natural gas stored in several sandstone lenses. Hydraulic fracturing is a stimulation technique used to maximize the flow and efficiency of natural gas transport to the surface from unconventional reservoirs. Once the formation is adequately cracked, 10-50% of the hydraulic fluid flows back to the surface . Our field team collected samples in Garfield County between 2013-2015 to measure methane, ozone precursors, and air toxics associated with natural gas extraction activities. Very few studies have provided direct observations of VOC emissions from individual well development activities. Emission rates of 48 VOCs and methane were determined using the tracer ratio method for three well development operations: drilling, hydraulic fracturing (fracking), and flowback for a subset of samples collected. Methane had mean emission rates of 1.57, 6.78, and 25.6 g s-1 for drilling, hydraulic fracturing, and flowback operations respectively, while toluene had mean emission rates of 1.24, 0.469, and 0.437 g s-1 for these operations. Measured emission rates were used to determine if specific VOCs were well correlated with each other and/or methane emission rates. Strong correlations between individual VOC emission rates and methane were investigated to assess whether methane emission rates might serve as useful surrogates for emission rates of individual VOCs, which are less easily measured. We found that methane and ethane appear to be emitted from the same sources for all operation types indicating that methane emission rates may be useful surrogates for ethane emission rates. Methane emission rates appear not to be very useful surrogates for heavier VOCs, including C5-C10 alkanes, alkenes, and aromatics. Concentration ratios of source-specific tracer compounds were investigated to determine the source signatures of individual operation types. We found that drilling emissions appear to be primarily influenced by combustion, while flowback emissions are primarily influenced by the release of natural gas and other substances from the well.
Keywords: oil and gas; volatile organic compounds; Piceance Basin; methane